2018
DOI: 10.3389/fnins.2018.00333
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Let-7f-5p Promotes Bone Marrow Mesenchymal Stem Cells Survival by Targeting Caspase-3 in Alzheimer Disease Model

Abstract: Widespread death of transplanted mesenchymal stem cells (MSCs) hampers the development of stem cell therapy for Alzheimer disease (AD). Cell pre-conditioning might help cope with this challenge. We tested whether let-7f-5p-modified MSCs could prolong the survival of MSCs after transplantation. When exposed to Aβ25−35 in vitro, MSCs showed significant early apoptosis with decrease in the let-7f-5p levels and increased caspase-3 expression. Upregulating microRNA let-7f-5p in MSCs alleviated Aβ25−35-induced apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…Similarly, it was also reported to attenuate endothelial cell damage in the OGD model, which further supported our results (Xiang et al, 2017). Besides, multiple evidences have proved that miRNAs, such as miR-203, let-7, miR-195, and miR-122, all exert the anti-apoptotic effect to protect against cell injury (Yang et al, 2015;Guo et al, 2018;Han et al, 2018;Cheng et al, 2019). Thus, miRNAs have the potential to become the novel therapeutic target for nervous system disease.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, it was also reported to attenuate endothelial cell damage in the OGD model, which further supported our results (Xiang et al, 2017). Besides, multiple evidences have proved that miRNAs, such as miR-203, let-7, miR-195, and miR-122, all exert the anti-apoptotic effect to protect against cell injury (Yang et al, 2015;Guo et al, 2018;Han et al, 2018;Cheng et al, 2019). Thus, miRNAs have the potential to become the novel therapeutic target for nervous system disease.…”
Section: Discussionsupporting
confidence: 87%
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…Stem cell-based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, 2017;Han et al, 2018;X. Wang, Ma, et al, 2018), DDD (Ahn et al, 2015;Beeravolu et al, 2018;Pereira et al, 2016;Perez-Cruet et al, 2018), MS (Harris et al, 2018;Nasri et al, 2018;Planchon et al, 2018), PD (Jamali et al, 2018;H.…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 2 more Smart Citations